Closed form expressions for two harmonic continued fractions. Issue 552 (16th October 2017) - Bunder, Martin; Tonien, Joseph
Abstract : A continued fraction is an expression of the form The expression can continue for ever, in which case it is called an infinite continued fraction, or it can stop after some term, when we call it a finite continued fraction. For irrational numbers, a continued fraction expansion often reveals beautiful number patterns which remain obscured in their decimal expansion. The interested reader is referred to [1] for a collection of many interesting continued fractions for famous mathematical constants.